2016
DOI: 10.1371/journal.pone.0168190
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Blood Flow Measurements in Healthy White Subjects Using Laser Speckle Flowgraphy

Abstract: PurposeTo assess the feasibility and reliability of Laser Speckle Flowgraphy (LSFG) to measure ocular perfusion in a sample of healthy white subjects and to elucidate the age-dependence of the parameters obtained.MethodsThis cross-sectional study included 80 eyes of 80 healthy, non-smoking white subjects of Western European descent between 19 and 79 years of age. A commercial LSFG instrument was applied to measure ocular blood flow at the optic nerve head (ONH) three successive times before and after pharmacol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
95
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(114 citation statements)
references
References 50 publications
14
95
1
4
Order By: Relevance
“…Furthermore, they suggested that tissue area falling rate is the only independent factor indicating age. Luft et al reproduced the same results for white subjects of Western European descent [50]. Our study also indicates significant increase in falling rate, and decrease in BOT in tissue area 10 minutes after water intake.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, they suggested that tissue area falling rate is the only independent factor indicating age. Luft et al reproduced the same results for white subjects of Western European descent [50]. Our study also indicates significant increase in falling rate, and decrease in BOT in tissue area 10 minutes after water intake.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, rising rate has also been found significant at 20 and 60 minutes after WDT. Luft et al have presented that the rising rate must be carefully considered pertaining to its moderate level of repeatability [50]. We have also observed an irregular trend for rising rate.…”
Section: Resultssupporting
confidence: 58%
“…A similar explanation for the rising rate and BOS values was obtained from the waveform analysis [19, 22, 32, 33]. All of the measurements were taken with the patients in the seated position, and pupils were dilated with 0.5% tropicamide eye drops.…”
Section: Methodsmentioning
confidence: 86%
“…In light of those findings, we hypothesized that the pulse waveform obtained from LSFG may reflect not only peripheral vascular dynamics but also cardiac vasculature dynamics. It was reported that the coefficient of variance for the rising rate and BOS measured by LSFG under pupil dilation were 2.62 and 5.67, respectively [33]. Thus, the rising rate and BOS, which comprise the pulse waveform of LSFG, have a highly reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…,b; Luft et al. ,b). Laser speckle flowgraphy has contributed to our understanding of the association of ocular BF with glaucoma pathophysiology by showing that MBR is associated with structure and function in glaucoma (Aizawa et al.…”
Section: Introductionmentioning
confidence: 99%